Further clinical and molecular delineation of the 15q24 microdeletion syndrome. Issue 2 (17th December 2011) - Mefford, Heather C; Rosenfeld, Jill A; Shur, Natasha; Slavotinek, Anne M; Cox, Victoria A; Hennekam, Raoul C; Firth, Helen V; Willatt, Lionel; Wheeler, Patricia; Morrow, Eric M; Cook, Joseph; Sullivan, Rachel; et al.
Abstract : Background: Chromosome 15q24 microdeletion syndrome is a rare genomic disorder characterised by intellectual disability, growth retardation, unusual facial morphology and other anomalies. To date, 20 patients have been reported; 18 have had detailed breakpoint analysis. Aim: To further delineate the features of the 15q24 microdeletion syndrome, the clinical and molecular characterisation of fifteen patients with deletions in the 15q24 region was performed, nearly doubling the number of reported patients. Methods: Breakpoints were characterised using a custom, high-density array comparative hybridisation platform, and detailed phenotype information was collected for each patient. Results: Nine distinct deletions with different breakpoints ranging in size from 266 kb to 3.75 Mb were identified. The majority of breakpoints lie within segmental duplication (SD) blocks. Low sequence identity and large intervals of unique sequence between SD blocks likely contribute to the rarity of 15q24 deletions, which occur 8–10 times less frequently than 1q21 or 15q13 microdeletions in our series. Two small, atypical deletions were identified within the region that help delineate the critical region for the core phenotype in the 15q24 microdeletion syndrome. Conclusion: The molecular characterisation of these patients suggests that the core cognitive features of the 15q24 microdeletion syndrome, including developmental delays and severe speech problems, are largely due to deletion of genes in a 1.1–Mb critical region. However, genes just distal to the critical region also play an important role in cognition and in the development of characteristic facial features associated with 15q24 deletions. Clearly, deletions in the 15q24 region are variable in size and extent. Knowledge of the breakpoints and size of deletion combined with the natural history and medical problems of our patients provide insights that will inform management guidelines. Based on common phenotypic features, all patients with 15q24 microdeletions should receive a thorough neurodevelopmental evaluation, physical, occupational and speech therapies, and regular audiologic and ophthalmologic screening.